Progression from an Immature Teratoma with Miliary Gliomatosis Peritonei to Growing Teratoma Syndrome with Nodular Gliomatosis Peritonei - Yuh-Lin Hsieh; Chin-Su Liu (Elsevier, 2009)
A 4½-year-old girl presented with an incompletely resected, huge, immature abdominal teratoma, elevated serum alpha-fetoprotein (AFP), and numerous miliary gliomatosis peritonei (GP). Two courses of chemotherapy resulted in normalization of her AFP level and marked tumor shrinkage. Further chemotherapy was interrupted by complications. During treatment for these complications, ascites increased and the tumor enlarged, but serum AFP remained within the normal range. Second-look surgery revealed that the tumor had changed histologically to a mature teratoma, and GP had enlarged to nodular size, causing massive ascites. The still incompletely resected, growing mature teratoma was reduced with inter-feron. Nodular GP and ascites slowly regressed with interferon use, and finally disappeared after several months. One residual mass thought to be GP was reduced by gamma-knife surgery 3 years later.